Self-expanding metal stents for anastomotic leaks after upper gastrointestinal cancer surgery - Liesenfeld, Lukas; Schmidt, Thomas; Zhang-Hagenlocher, Christine; Sauer, Peter; Diener, Markus K.; Müller, Beat P.; Hackert, Thilo; Büchler, Markus W.; Schaible, Anja (Journal of surgical research, 2021)
Background - Anastomotic leakage (AL) is a common and severe complication after upper gastrointestinal (UGI) surgery. Although evidence is scarce, endoscopic deployed self-expanding metal stents (SEMS) are well-established for the management of AL in UGI surgery. The present study aimed to evaluate the feasibility, effectiveness, and safety of SEMS in terms of success, mortality, and morbidity in patients with AL after UGI cancer surgery. - Materials and Methods - Patients with AL after primary UGI cancer surgery were retrospectively analyzed with regard to demographics, disease, surgical and endoscopic procedures, and complications. Stent treatment success was divided into technical, primary (within 72 hours of stent deployment), sustained (after 72 hours of stent deployment), and sealing success. - Results - In a total of 63 patients, 74 stents were used and 11 were deployed in endoscopic reinterventions. Stent deployment was successful in all patients. Primary and sustained success rates were 68.3% (n = 43) and 65.1% (n = 41), respectively. Of the primarily successfully treated patients, 87.8% remained successfully treated. If primary treatment was unsuccessful, it remained unsuccessful in 66.6% of the patients (P = 0.002). Final sealing of the leakage was observed in 65.1% of patients (n = 41). Longer stent shafts and wider stent end widths were correlated with successful stent treatment (P < 0.05). - Conclusion - SEMS are a safe and sufficient tool in the treatment of AL after UGI cancer surgery. Treatment success is improved with longer stent shafts and wider stent end widths. Switching to alternative treatments is strongly suggested if signs of persistent leakage are present beyond 72 hours after stent placement, as this is highly indicative of sustained stent failure.